Fringe structures and tunable bandgap width of 2D boron nitride nanosheets - Feng, Peter; Sajjad, Muhammad; Li, Eric Yiming; Zhang, Hongxin; Chu, Jin; Aldalbahi, Ali; Morell, Gerardo (Beilstein Journal of Nanotechnology, 2014)
We report studies of the surface fringe structures and tunable bandgap width of atomic-thin boron nitride nanosheets (BNNSs). BNNSs are synthesized by using digitally controlled pulse deposition techniques. The nanoscale morphologies of BNNSs are characterized by using scanning electron microscope (SEM), and transmission electron microscopy (TEM). In general, the BNNSs appear microscopically flat in the case of low temperature synthesis, whereas at high temperature conditions, it yields various curved structures. Experimental data reveal the evolutions of fringe structures. Functionalization of the BNNSs is completed with hydrogen plasma beam source in order to efficiently control bandgap width. The characterizations are based on Raman scattering spectroscopy, X-ray diffraction (XRD), and FTIR transmittance spectra. Red shifts of spectral lines are clearly visible after the functionalization, indicating the bandgap width of the BNNSs has been changed. However, simple treatments with hydrogen gas do not affect the bandgap width of the BNNSs.
Keywords: boron nitride sheets; fringe patterns; functionalization; tunable bandgap width